HPV Status and Its Correlation with BCL2, p21, p53, Rb, and Survivin Expression in Breast Cancer in a Chinese Population. (20th December 2017) - Wang, Ya-Wen; Zhang, Kai; Zhao, Song; Lv, Yanrong; Zhu, Jiang; Liu, Huantao; Feng, Jinbo; Liang, Weili; Ma, Rong; Wang, Jianli
Abstract : Despite recent evidence, the role of human papillomavirus (HPV) in breast carcinogenesis is controversial. The correlations of HPV infection with the clinicopathological features of breast cancer and the expression of cell cycle/apoptosis-associated proteins have not been well elucidated. In this study, we sought to determine the prevalence of high-risk HPVs (HR-HPVs) infection and BCL2, p21, p53, Rb, and survivin expression in breast cancer patients and to investigate the relationship of HPV with these cancer-related proteins, in an attempt to clarify the potential mechanism of HPV in breast cancer pathogenesis. HPV presence in 81 fresh breast cancer tissues was determined by hybrid capture 2 (HC2) assay, and expression of BCL2, p21, p53, Rb, and survivin was detected by immunohistochemistry. Here we showed that fourteen (17.3%) patients were HR-HPV positive. HPV infection demonstrated no significant correlation with the clinicopathological characteristics of breast cancer. HPV-positive tumors showed significantly higher BCL2 and lower p53 expression than HPV-negative tumors. Expression of p21, Rb, and survivin was not associated with HPV status. Our results suggest a possible role of HR-HPV in breast cancer carcinogenesis, in which BCL2 and p53 may be involved.